Evaluation of post-surgical stability in skeletal class II patients with idiopathic condylar resorption treated with functional splint therapy. Issue 3 (March 2020) - Ha, Nayoung; Hong, Yueyang; Qu, Luyao; Chung, Miri; Qu, Ranyi; Cai, Xieyi; Fang, Bing; Jiang, Lingyong
Abstract: Purpose: To assess postsurgical stability of mandibular advancement combined with orthodontic treatment, following functional splint therapy, in patients with idiopathic condylar resorption (ICR). Patients and methods: Sixteen patients who were treated with functional splint therapy followed by orthognathic surgery combined with orthodontic treatment between 2010 and 2017 were included in this retrospective study. The primary outcome variable was skeletal stability, measured on the y -axis to point B ( y -axis–B). Cephalometric analysis, including measurement of temporomandibular joint spaces, was carried out on serial magnetic resonance images (MRI) prior to orthognathic surgery (T0), immediately after surgery (T1), and after at least 1 year of follow-up (T2). The differences in the data between time points were compared using statistical analyses. Results: All patients obtained an esthetic facial profile after orthognathic surgery, with normal occlusion as well as normal protrusive and laterotrusive excursion after treatment. Mean advancement of the mandible immediately following surgery ( y -axis–B, T1 − T0) was 7.28 ± 5.79 mm. This was the only skeletal measurement that showed a sagittal positional change of the mandible. Mean backward movement (T2 − T1) was −1.04 ± 2.35 mm ( p 2  = 0.116). Thirteen out of 16 patients experienced no postsurgical relapse or less than 2 mm of mandibular backward movement (81.25%), while two out of 16 patients showed more than 2 mm of mandibular backward movement (12.5%). Conclusions: Patients who underwent mandibular advancement combined with orthodontic treatment, following functional splint therapy, exhibited a stable mandibular position at the 1-year follow-up. This study indicated that functional splint therapy prior to orthognathic surgery for mandibular advancement may be a good adjuvant treatment for ICR patients.